MENUMBUHKAN BUDAYA MEMBACA ANAK-ANAK PEDESAAN MELALUI PENGAKTIFAN KEMBALI PERPUSTAKAAN KOMUNITAS DI SRIKATON PONDOK KELAPA BENGKULU TENGAH - Sri Handayani Hanum; Purwaka .; Purwadi Eka Tjahjono; Heni Nopianti (DHARMA RAFLESIA, 2017)
This community service activity was conducted in the Village of Srikaton, Sub-District of Pondok Kelapa, Central Bengkulu District. The aim is to increase reading enthusiasmamong school-age children. Therefore, the target of this activity is the children of localvillages and surrounding areas that are still studying in primary and secondary educationlevels. This activity focused on increasing children's interest in the use of village librarythat had been passive, so that the library is active again. This service activity was carriedout in the form of a drawing competition/coloring pictures, writing stories, and storytelling. In realizing the goal of this community service activity, steps that have been madeare: (a) a dialogue between the team of this community service with some village officersand community leaders to discuss the reactivation of the village library of Srikaton; (b) theplacement of a volunteer who is competent in managing the village library; (c) thedissemination of library services, (d) the donation of recent books to the local villagelibrary and the library of SD Negeri 7 Srikaton (State Primary School 7 Srikaton); (e)conducting an educational event in the village library, (f) monitoring and advising on the management and library services to the village library of Srikaton and the school libraryof SD Negeri 7 Srikaton. The results of this community service activity are as follows: thevillage library, which previously was passive, has been active again since 17August, 2014.The activation was done by the placement of a voluntary librarian in this library. Libraryis open two days a week, which is Saturday from 16:00 to 18:00 and Sundays from 10:00to 13:30. The socialization of the village library services was conducted by the teamthrough a local person, who is the village library volunteer, and the teachers of SD Negeri7 Srikaton. The team also donated 86 titles of books (143copies) worth Rp5.029.800,-.Several educative competition activities based on library collections were done by holding a drawing/coloring contest, summarize the story books, and story-telling. Monitoring andproviding consultation on library management conducted by the team once a monthperiodically from May 2014 until April 2015.Keywords: Community Library Reactivation, School Age Children, Reading Enthusiasm